2014
DOI: 10.1074/jbc.m114.587527
|View full text |Cite
|
Sign up to set email alerts
|

Interactions with Actin Monomers, Actin Filaments, and Arp2/3 Complex Define the Roles of WASP Family Proteins and Cortactin in Coordinately Regulating Branched Actin Networks

Abstract: Background: How cortactin and WASP proteins coordinately regulate branched actin assembly is poorly understood. Results: The Arp2/3 complex-and actin-interacting regions of cortactin and WASP proteins are functionally distinct and tailored to their regulatory roles. Conclusion: Mechanistic distinctions between activators are important in allowing coordinate regulation of branched actin networks. Significance: Understanding mechanistic distinctions between activators is required to understand cellular structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 77 publications
3
46
0
1
Order By: Relevance
“…The direction of synaptic morphologic changes, to retract or to sprout, may depend on the balance of actin depolymerization and polymerization, the latter being regulated by Rac/Cdc42 pathways as stated above. [39][40][41] In our study, the contribution of Pak to both retraction and growth suggests that although process growth in isolated rod cells appears to be a late-stage development, the Rac/Cdc42 growth pathways may be activated early on. However, when and where actin filament nucleation and elongation begins still needs to be examined.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The direction of synaptic morphologic changes, to retract or to sprout, may depend on the balance of actin depolymerization and polymerization, the latter being regulated by Rac/Cdc42 pathways as stated above. [39][40][41] In our study, the contribution of Pak to both retraction and growth suggests that although process growth in isolated rod cells appears to be a late-stage development, the Rac/Cdc42 growth pathways may be activated early on. However, when and where actin filament nucleation and elongation begins still needs to be examined.…”
Section: Discussionmentioning
confidence: 58%
“…19,20,[35][36][37] The role of Rac and Cdc42 in promoting growth is achieved through actin filament nucleation by ARP2/3 and Pak activities. [39][40][41] We speculate that the role of Pak in retraction may be to promote depolymerization of actin filaments through LIMK activity. Such depolymerization would be necessary to form new actin cytoskeleton in either filopodia or lamellipodia.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although little is known about this class of NPFs, we previously used the cross-linking assay to show that WDS protein Dip1 stimulates formation of the shortpitch conformation, and our data here suggest this stimulation is sufficient for Dip1-mediated activation of the complex (5). Like the WDS family proteins, type II NPFs such as cortactin and fission yeast myosin I interact with the Arp2/3 complex and actin filaments but not with actin monomers (37,(42)(43)(44). Unlike WDS proteins, type II NPFs are generally weak activators on their own (7).…”
Section: Discussionmentioning
confidence: 60%
“…It was previously thought that Arp2/3 complex was activated by a single NPF, but a series of studies have now shown that the complex is maximally activated by two NPFs [47-50]. Thus, like in other nucleators, the WH2 domains of NPFs play an auxiliary role in nucleation, by delivering actin subunits at the barbed end of the nucleus formed by Arp2 and Arp3 ( Figure 5 ).…”
Section: Opinionmentioning
confidence: 95%